Geomorphological evolution revealed by aeolian sedimentary structure in Badain Jaran Desert on Alxa Plateau, Northwest China - Bai, Yang; Wang, Nai’ang; Liao, Kongtai; Klenk, Patrick (Chinese geographical science, 2011)
The Badain Jaran Desert, located in the Alxa Plateau, Northwest China, features mega-dunes and a unique dune-lake alternation landscape. This paper presented the aeolian sediment structures of three representative dunes in the Badain Jaran Desert using ground-penetrating radar (GPR). We processed and analyzed the GPR data and investigated the feasibility of using integrated GPR and sedimentological data to reconstruct dunes structure, sedimentary environment and geomorphological evolution. The results show that the internal structures of star dune and transverse dune represent various stages of mega-dune evolution: the main deposition processes of mega-dune are similar to those of transverse dunes but have a more complicated mechanism of sand transport and deposition because of the superimposition of dunes; the upper section of the mega-dune has a structure similar to that of star dune, with vertical aggradations on top. Diffraction hyperbolae in the GPR profile indicates that the presence of ancient dunes characterized by calcareous cementation layers is involved in the maintenance of mega-dunes, and water levels, shown by continuous, sub-horizontal GPR reflections, are supposed to be closely related to mega-dunes and the interdune lakes. Outcrop of wet sand and horizontal stratifications on the GPR image indicate moisture potentials with different levels inside mega-dunes. The multiplex geomorphology in the Badain Jaran Desert is the result of global climatic undulation, the unique geographical location, the geological structural features, etc.